The presence of national identity elements in Arabic language texts at the secondary level.: (the third year books reading) - Mechta, Mehdi (Journal of Human Sciences, 2021)
In this article, we will try talk about the algerian educational system and learn about its support for the third year students national identity) and discuss:(history, religion and language) in the Arabic language texts and discussing wether this approach focused on the national identity and its elements as a main topic in the Arabic language texts for the secondary level.